EMOTIONAL LANDSCAPE OF THE IVO ANDRIĆ’S NOVEL THE DAMNED YARD (Heritage, 2024)
Our research, presented in this paper, aimed to apply the concept of emotional landscape, which was introduced into the theory of literature by affective narratologists, in the interpretation of Andrić's short novel The Damned Yard. We devoted the initial part of the paper to elucidating the narrative profile of the novel and analyzing the narrator's emotions. We pointed out that there is a narrative instance of the omniscient narrator who occasionally leaves the relay of narration to other characters. We emphasized that it is impossible to talk about the emotions of such a narrative instance, but that it is possible to determine that the story is told from an emotional system connected to the emotions of fear of death and faith in life. The main point of the research was the interpretation of the emotional profile of the heroes, i.e. their manifestations of fear, love, sadness and other complex emotions, actualized in Andrić's novel. In the analysis, we examined different types of listed feelings, distinguishing the ways in which they are narrated, which may involve the transposition of the emotion through the thoughts and actions of the hero, facial expression, body position, uncontrolled vocalization or other somatic reactions. Looking at different emotional manifestations, we aimed to demonstrate the essential dependence of the narrative, motivation and chronotope on the emotions of the narrative instances and the actors themselves. We ended the observation of the novel's emotional landscape by illuminating the readers' emotions and contextualizing empathy as their dominant response to the read text. We explained that the possibility of readers' empathetic response to sad, anxious, fearful and pessimistic emotions is conditioned by the possibility of identification of readers with the hero, the socio-historical context of reading, but also the great aesthetic value that the author achieved in his text.
Keywords: The Damned Yard, Ivo Andrić, emotional landscape, affective narratology, narrator's emotions, hero's emotions, readers' emotions, fear, love, sadness